A Framework Integrating Operational Management and Accommodation in Karang Asam Festival Planning: Kerangka Integratif antara Manajemen Operasional dan Pengelolaan Akomodasi dalam Perencanaan Festival Karang Asam - Wisanggeni Agus Priyanto; Hanif Hasan; Sri Wulan Damayati; I Made Oka Mertajayanto; Zulkifli Harahap (Journal of Event, Travel and Tour Management, 2026)
Community based festivals can strengthen local development and cultural sustainability, yet research rarely explains how operational management and accommodation can be integrated in grassroots festival planning. This study proposes an integrated planning framework for the Karang Asam Festival in Muara Enim, South Sumatra. A qualitative case study was conducted using semi structured interviews, field observations, and document review across the pre event, event, and post event phases. The data were analyzed thematically to identify patterns in operational planning (logistics, communication, site management, and risk handling) and accommodation management using the Guest Service Cycle perspective. Findings show a Blended governance model: basic coordination exists, but many operational activities depend on experience rather than written Standard Operating Procedures. Accommodation is organized through a mixed system hotels for key performers and community managed homestays for other guests yet minimum service standards and centralized coordination remain limited, leading to inconsistent service quality. Despite these constraints, integration between operations and accommodation is maintained through strong community participation, social trust, and collective ownership. The study recommends gradual improvements, including simplified SOPs, better schedule control, minimum homestay standards, and a lightweight feedback mechanism. This framework supports more reliable operations and more consistent guest experience while preserving community-based governance.